Ovarian tissue bank for fertility preservation and anti-menopause hormone replacement - Chen, Jing; Han, Yan; Shi, Wenjie; Yan, Xiaohong; Shi, Yingying; Yang, Ye; Gao, Hong; Li, Youzhu (Frontiers in Endocrinology, 2022)
Traditional fertility preservation methods such as embryo or oocyte cryopreservation cannot meet the needs of a cancer patient or personal reasons. The cryopreservation of ovarian tissue can be an alternative and has become a hot spot to preserve fertility or hormone replacement. The freezing of ovarian tissue can be carried out at any time without ovarian hyperstimulation to retrieve follicles. It is an ideal strategy to preserve reproductive function for children, adolescent cancer patients, and patients who are in urgent need of cancer treatment. With the increasing demands of women with premature ovarian failure or in menopause, ovarian tissue transplantation also is an alternative for hormone replacement that can provide physiological doses of hormone levels, which can avoid a series of risks such as thrombosis, breast cancer, or another hormone-dependent tumor caused by oral hormone replacement. Hence, ovarian tissue bank can be regarded as a mainstream strategy for fertility preservation and anti-menopause hormone replacement in further clinical investigation.